IMPROVEMENT ANALYSIS OF VISIOFROTH CAMERA IN ROUGHER FLOTATION CIRCUIT C3 & C4 AT PT FREEPORT INDONESIA - (NIM: 29109131); Pembimbing Thesis: Prof. Togar M Simatupang, Ph.D, ERWAN
PT Freeport Indonesia (PTFI) has installed 172 vision cameras (VisioFrothTM) at C1 to C4 concentrator. The camera installed at each cell in rougher flotation circuit to measure the froth appearance. Information from camera, froth velocity, is used to determine the optimum mass pull at each cell to maximize the regrind circuit capacity. This philosophy will deliver an opportunity to maximize rougher recovery in flotation circuit. Installation of the system delivered a 1.0% incremental recovery benefit, whilst implementation of novel control logic has led to additional 2.4% increased in rougher recovery. PTFI production rate in 2010 implies 1.0% improvement of copper recovery is equivalent to $41.64M increasing annual revenue. In 2009, the degradation of camera reliability indicated the loss opportunity to improve rougher recovery. The low impact scenario, 0.1% loss opportunity in copper recovery, which deliver an additional $3.0M is used as a baseline. The root cause to low camera reliability is age of USB camera system, USB cable extender and USB Hub. Three alternatives business solution are discussed: keep maintain the current USB system, replace USB camera system with new USB camera system, and demolish USB camera system with replacement to IP camera technology. The best alternative solution is selected using a SMART analysis base on criteria: Financial Analysis, Future Reliability, Maintenance Time, and Future Potential for Development. IP camera Technology solution is favorable to overcome the current problem. The implementation plan will be carried out in C4 concentrator as the first project. There are four phases: Engineering and construction, commissioning, control migration, and evaluation. Following project is to C3, C1, and C2 concentrator.